The Safer Internet Programme as an electronic aspect of the EU Communication Policy - Карпчук, Наталія Петрівна; Karpchuk, Nataliia P. (Госпотребстандарт Украины; Национальное агентство аккредитации Украины; Национальная металлургическая академия Украины; Технический университет - Варна; Государственный институт подготовки и переподготовки кадров промышленности, 2011)
The EU Information and Communication Policy is inseparable from digital connections. Electronic aspects in the European development, communication as well, are researched.
Keywords: European Union’s information and communication; White Paper on a European Communication Policy